Polityka globalna jako czynnik lokalnych aktywności i zmian społecznych = Global politics as a factor influencing local activity and social change - Wyleżałek, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article aims to present the relationship between global politics, which re?ects di?erent visions of the world order, and the actions of local politicians and activists, which can bring about social change. The author of the article explores the sources of growing social divisions and points to contemporary politics, which is increasingly turning into "undemocratic liberalism" (which is likely to be a tool for a uni?ed vision of the world) and "illiberal democracy" (which is becoming an unsuccessful antidote to the backstage mechanisms of global politics), ?tting ideologically into activities aimed at strengthening national economies.
Keywords: porządek światowy; polityka globalna; gracze ekonomiczni; wojny kulturowe; aktywności lokalne; zmiana społeczna; world order; global politics; economic actors; cultural wars; local activities; social change